Are There Tax Effects in the Relative Pricing of u.s. Government Bonds? - Green, Richard C; Odegaard, Bernt A (Journal of Finance, 1997)
The authors investigate the impact of the Tax Reform Act of 1986 on the relative pricing of U.S. Treasury Bonds. They obtain positive statistically and economically significant estimates for the implicit tax rates of a 'representative' investor in the late 1970s and early 1980s. After the 1986 tax reform, the point estimates for the tax rate are close to zero. Tests for a regime shift associated with the 1986 tax reform support the hypothesis that this event largely eliminated tax effects from the term structure. The authors discuss both institutional and statutory explanations for this change.